D-orbital Reconstruction Achieves Low Charge Overpotential in Li-oxygen Batteries - Yin Zhou; Kun Yin; Yingying Huang; Jiapei Li; Anquan Zhu; Dewu Lin; Guoqiang Gan; Jianfang Zhang; Kai Liu; Tian Zhang; Kunlun Liu; Chuhao Luan; et al. (Nature Communications)
Abstract Charge overpotential for oxygen evolution reaction is a crucial parameter for the energy conversion efficiency of lithium-oxygen (Li-O2) batteries. So far, the realization of low charge overpotential via catalyst design is a grand challenge in this field, which usually exceeds 0.25 V. Herein, we report an orbital reconstruction strategy to significantly decrease the charge overpotential to the low 0.11 V by employing PdCo nanosheet catalyst under a low-loading mass (0.3 mg/cm2) and capacity (0.3 mAh/cm2). Experimental and theoretical calculations demonstrate that the precise d-d orbital coupling (d xz-d xz, d yz-d yz and d z 2-d z 2) between the low-electronegativity Co and Pd leads to the reconstruction of Pd 4 d orbitals in PdCo nanosheets, thereby resulting in a downward shift of all the three active Pd 4 d orbitals (d z 2, d xz and d yz) relative to that of Pd nanosheets. Furthermore, the highest energy level of the Pd 4d z 2 orbital in PdCo is lower than the lowest energy levels of the Pd 4d xz and 4d yz orbitals in pure Pd, significantly decreasing the charge activation energy and achieving a highest energy conversion efficiency of 91%. This finding provides the orbital-level tuning into rational design of highly efficient electrocatalysts for Li-O2 batteries.